OF PROCESSING PARAMETERS OF VIBRATION DURING WELDING ON THE PROPERTIES OF WELDED JOINTS - R. G. Rizvanov; A. M. Fayrushin; D. V. Karetnikov (Литьë и металлургия)
The researches of influence of vibrating processing regimes on mechanical and other properties of the welded joints received by fusion welding are carried out on the basis of the literary analysis of the works devoted to influence of vibrating oscillations on melted and crystallizing metal.